Symposium on Obesity and Asthma –November 2, 2006 - Louis-Philippe Boulet; Qutayba Hamid (Canadian Respiratory Journal)
Asthma and obesity are frequently associated, and obesity has been considered a factor contributing to both an increase in severity of asthma and to its development. The present document summarizes the proceedings of a symposium held in Montreal, Quebec, on November 2, 2006, under the auspices of the Réseau en santé respiratoire du Fonds de la recherche en santé du Québec in collaboration with the McGill University – Strauss Severe Asthma Program, Université Laval (Quebec City) and Université de Montréal. It includes an overview of the various aspects of the relationships between asthma and obesity with regard to animal models; genetic, hormonal and physiological determinants; influence of comorbidities (eg, sleep apnea syndrome); epidemiology; clinical and psychological features; and management of asthma in the obese population.